The impact of coronavirus disease 2019 (COVID-19) response on hospital infection prevention programs and practices in the southeastern United States. (2nd February 2023) - Advani, Sonali D.; Cromer, Andrea; Wood, Brittain; Baker, Esther; Crawford, Kathryn L.; Crane, Linda; Roach, Linda; Padgette, Polly; Dodds-Ashley, Elizabeth; Kalu, Ibukunoluwa C.; Weber, David J.; Sickbert-Bennett, Emily; et al.
Abstract: Initial assessments of coronavirus disease 2019 (COVID-19) preparedness revealed resource shortages and variations in infection prevention policies across US hospitals. Our follow-up survey revealed improvement in resource availability, increase in testing capacity, and uniformity in infection prevention policies. Most importantly, the survey highlighted an increase in staffing shortages and use of travel nursing.